Prevalence of mental disorders and work ability among unemployed individuals in Germany: a register-based analysis of socio-medical assessments by the Federal Employment Agency between 2016 and 2021 - Patrik Roser; Kirsi Manz; Norbert Scherbaum; Gabriele Lotz-Metz; Andreas G. Franke (BMC Public Health)
Abstract Background The interactions between unemployment and mental health are complex. However, broad and current epidemiological data about the mental health status of unemployed individuals in Germany are scarce. This study aimed to evaluate the prevalence rates of mental disorders and work ability among all unemployed people who underwent socio-medical assessment by the Federal Employment Agency (FEA). Methods Socio-medical assessments between 2016 and 2021 were taken from the FEA database and analyzed regarding sociodemographic characteristics, mental disorders and work ability. Standard descriptive statistics were used to analyze the data. Results A total of 4,249,028 unemployed individuals were assessed. Of these, 2,213,048 persons (52.1%) had at least one psychiatric diagnosis (mean age 40.6 ± 13.5 years, 51.7% female). Mood disorders (53.9%), neurotic, stress-related and somatoform disorders (43.9%), as well as substance use disorders (15.3%) showed the highest prevalence rates among mental disorders and accounted for about 80% of all psychiatric diagnoses. About 40% of them were evaluated to be able to work full time. Conclusions Psychiatric morbidity among unemployed people is high. However, a significant proportion of them was assessed to be able to return to the labor market. Therefore, close collaborations between unemployment agencies and mental health care institutions as well as specific re-integration programs including supported job placement and vocational training, long-term job coaching as well as integrated mental health care are required in order to improve mental health status, prevent further chronification, avoid labor market exit, and increase employment rate.